And so I roar : a novel - Daré, Abi (Dutton, an imprint of Penguin Random House, 2024)
"A stunning, heartwrenching new novel from Abi Daré, New York Times bestselling author of The Girl with the Louding Voice. When Tia accidentally overhears a whispered conversation between her mother--terminally ill and lying in a hospital bed in Port Harcourt, Nigeria--and her aunt, the repercussions will send her on a desperate quest to uncover a secret her mother has been hiding for nearly two decades. Back home in Lagos a few days later, Adunni, a plucky fourteen-year-old runaway, is lying awake in Tia's guest room. Having escaped from her rural village in a desperate bid to seek a better future, she's finally found refuge with Tia, who has helped her enroll in school. It's always been Adunni's dream to get an education, and she's bursting with excitement. Suddenly, there's a horrible knocking at the front gate. . . . It's only the beginning of a harrowing ordeal that will see Tia forced to make a terrible choice between protecting Adunni or finally learning the truth behind the secret her mother has hidden from her. And Adunni will learn that her "louding voice," as she calls it, is more important than ever, as she must advocate to save not only herself but all the young women of her home village, Ikati. If she succeeds, she may transform Ikati into a place where girls are allowed to claim the bright futures they deserve--and shout their stories to the world"--